Hardware-software complex of informing passengers of forecasted route transport arrival at stop; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Pogrebnoy V. Yu. Vadim Yurievich (Information technologies in Mechanical Engineering, 2017)
Title screen